THE ROLE OF RADIO BROADCASTS IN THE DEVELOPMENT OF READING AMONG THE POPULATION - Kimsanboev Rakhmonjon Valizoda (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article discusses the role of radio broadcasting in the development of reading among the population. The article also talks about the analytical results of broadcasting programs aimed at improving the culture of reading among young people through "Mahalla" radio.